2002
DOI: 10.1103/physrevd.66.023516
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of the cosmic microwave background anisotropy to initial conditions in quintessence cosmology

Abstract: We analyze the evolution of energy density fluctuations in cosmological scenarios with a mixture of cold dark matter and quintessence, in which the quintessence field is modeled by a constant equation of state. We obtain analytic expressions for the time evolution of the quintessence perturbations in models with light fields. The fluctuations behave analogously to a driven harmonic oscillator, where the driving term arises from the inhomogeneities in the surrounding cosmological fluid. We demonstrate that the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 26 publications
3
63
0
Order By: Relevance
“…At subhorizon scales the effective (geometrical in our case) dark energy component is expected to be smooth and thus it is fair to consider perturbations only on the matter component of the cosmic fluid [38]. The evolution equation of the matter fluctuations δ m ≡ δρ m /ρ m , for cosmological models where the dark energy fluid has a vanishing anisotropic stress and the matter fluid is not coupled to other matter species (see Refs.…”
Section: The Linear Matter Fluctuationsmentioning
confidence: 99%
“…At subhorizon scales the effective (geometrical in our case) dark energy component is expected to be smooth and thus it is fair to consider perturbations only on the matter component of the cosmic fluid [38]. The evolution equation of the matter fluctuations δ m ≡ δρ m /ρ m , for cosmological models where the dark energy fluid has a vanishing anisotropic stress and the matter fluid is not coupled to other matter species (see Refs.…”
Section: The Linear Matter Fluctuationsmentioning
confidence: 99%
“…(6) and (7). Combining these equations, the evolution of density perturbations in the IQ field are described by a driven damped harmonic oscillator, where the driving term is the gravitational field [27]. After a brief transient period, the evolution is dominated by the inhomogeneous solution and is insensitive to the initial amplitude.…”
Section: Observational Constraints On the Matter-quintessence Comentioning
confidence: 99%
“…Although it has been shown that the dark energy fluid does not cluster on scales smaller than 100Mpc [86], it is also interesting to consider the case when the dark energy clusters along with the dark matter. Such a behavior is expected in models of interacting dark energy with dark matter and may also be a result of the gravitational interaction between nonlinearly clustered dark matter and dark energy.…”
Section: B Inhomogeneous Dark Energymentioning
confidence: 99%